Experimental Study on Morphology of Tension and Shearing Fractures for Red Sandstone - Pang, Lei; Ren, Fuqiang (Geotechnical and geological engineering, 2022)
In order to explore the influence of tensile and shear failure modes on the fracture surface morphology of red sandstone, the Brazilian splitting tests and direct shear tests were carried out. The tension and shearing fractures of sandstone were scanned by PS50 three-dimensional surface morphology system. The variation of fracture morphology parameters was analyzed by morphology evaluation index, and the difference of fracture morphology under different failure modes was determined. Additionally, the internal influence mechanism of different failure modes on the fracture surface morphology was discussed. The results show that the elevation of shear fracture morphology changes dramatically, and the convex and concave parts are obvious and discrete. However, the fluctuation of tension fracture is relatively flat, and tends to be smooth.